Relationship Between Population Size and Symbiont Fungus Culture Volume in Colonies of Acromyrmex balzani (Hymenoptera: Formicidae) - Caldato, Nadia [UNESP]; Protti de Andrade, Ana Paula [UNESP]; Forti, Luiz Carlos [UNESP]; Barbieri, Rafael Forti [UNESP]; Santos Lopes, Juliane Floriano (California State University, 2010)
In order to quantify the population of Acromyrmex balzani Emery, 1890 nests and to verify whether the population dynamic of the colony is correlated with the symbiont fungus volume, the principal energy source of the colony, five nests located in grassland areas were evaluated. The nests were sprayed with neutral talcum powder to improve visualization and digging. The symbiont fungus and the entire population existent in the chambers were collected. The mean fungus volume and total nest population in excavated nests were, respectively, 74.76 ml and 1,095 individuals. Simple linear correlation analysis verified that the fungus volume grew proportionally to the number of individuals. Despite the correlation between fungus volume and population dynamic of colonies, the factors that determine this relationship are little known since other microorganisms live in association with the colony.
Keywords: symbiont fungus; population; nest chambers; leaf-cutting ants